2021
DOI: 10.1371/journal.pone.0247384
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive clinical and laboratory evaluation of 224 patients with persistent symptoms attributed to presumed tick-bite exposure

Abstract: Background Persistent symptoms attributed to presumed tick-bite exposure constitute an unresolved medical controversy. We evaluated whether Swedish adults who met the criteria for post-treatment Lyme disease syndrome (PTLDS) exhibited characteristics distinguishable from adults who did not, but who displayed similar symptoms and disease course after suspected previous tick-bite infection (TBI). Methods and findings During 2015–2018, 255 patients–referred to the Centre for Vector-borne Infections, Uppsala Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Although the study population was not selected for a history of tick bites, the frequency of Anaplasma IgG positivity in this work is virtually identical to the results of our study in patients with suspected PTLDS (12.6%). A very similar result (11%) was also found in the general adult population in southern Norway [46] and in patients with persistent symptoms attributed to suspected tick bite exposure in Sweden, where Anaplasma antibodies were detected in 12% of patients [47]. In a serological study in neighboring Poland, antibodies against Anaplasma were found in 11.8% of forest workers and in 9.4% of healthy control blood donors [48].…”
Section: Discussionsupporting
confidence: 68%
“…Although the study population was not selected for a history of tick bites, the frequency of Anaplasma IgG positivity in this work is virtually identical to the results of our study in patients with suspected PTLDS (12.6%). A very similar result (11%) was also found in the general adult population in southern Norway [46] and in patients with persistent symptoms attributed to suspected tick bite exposure in Sweden, where Anaplasma antibodies were detected in 12% of patients [47]. In a serological study in neighboring Poland, antibodies against Anaplasma were found in 11.8% of forest workers and in 9.4% of healthy control blood donors [48].…”
Section: Discussionsupporting
confidence: 68%
“…We conclude that to date, science has no alternative diagnostic tests to offer patients with persisting symptoms post-treatment besides the well-established ones recommended for investigation of LB. In a recently published report, however, it has been shown that symptoms that are often categorized as chronic LB in the general debate could not be uniquely linked to LB ( 86 ). Instead, ~20% of the total group of patients showed signs of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…We purposely selected participants from an exploratory study of human tick-borne infections conducted at the Center for Vector-borne Infections (CVI), Uppsala University Hospital, Uppsala, Sweden between October 2015 and December 2018 [24]. A total of 224 patients were enrolled in the principal study during this period.…”
Section: Study Populationmentioning
confidence: 99%
“…The other criteria were age ≥ 18 years; suspected tick-borne infection based on previous tick exposure; symptoms; laboratory findings; previous treatment for tick-borne infection; and/or suspicion of co-infection with other tick-borne infections. A summary of data on these patients has previously been published [24].…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation